2010
DOI: 10.2193/2009-560
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of Tree Cavities During Winter in a Northern Hardwood Forest

Abstract: Tree cavities likely vary in their thermal quality for cavity-nesting animals, which could be especially important during winter. We conducted a winter field experiment to test whether cavities vary either in their buffering capacity or in their mean temperature according to predictable characteristics. We found that cavities buffered temperature and that there was a lag effect in temperature that appeared to be related to heating and cooling. Diameter at breast height was the most important variable influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 22 publications
6
39
0
Order By: Relevance
“…An identical pattern was found in all studies done during the breeding season (papers referred to above, and Stains, 1961;Martin and Ghalambor, 1999;Wiebe, 2001), as well as in studies on roosting cavities carried out during the winter (Paclík and Weidinger, 2007;Coombs et al, 2010). Thus, tree cavities appear to dampen the daily temperature fluctuations and provide a much more stable thermal environment than the world outside.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…An identical pattern was found in all studies done during the breeding season (papers referred to above, and Stains, 1961;Martin and Ghalambor, 1999;Wiebe, 2001), as well as in studies on roosting cavities carried out during the winter (Paclík and Weidinger, 2007;Coombs et al, 2010). Thus, tree cavities appear to dampen the daily temperature fluctuations and provide a much more stable thermal environment than the world outside.…”
Section: Discussionsupporting
confidence: 62%
“…We presumed that different types of cavities would provide contrasting environments, but there are hardly any data to check this. Available data indicate, though, that air temperatures in cavities may depend on their locality and dimensions (Hooge et al, 1999;Wiebe, 2001;Sedgeley, 2001;Packlík and Weidinger, 2007;Rhodes et al, 2009;Coombs et al, 2010). Thus, by selecting cavities with appropriate attributes, the birds would able to adjust microclimatic conditions in cavities to their requirements, at least to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…One potential explanation for this finding is that the insulation properties of natural nest cavities are so superior to nest boxes that, even at high elevations, mountain bluebirds breeding in natural cavities rarely experience strong selection for high cold tolerance of eggs and young nestlings. Multiple studies (Coombs et al, 2010;Amat-Valera et al, 2014), including this study (Figure 1), have found that natural cavities are well-insulated while internal temperatures of nest boxes do not differ from ambient temperatures. Thus, it will be interesting in future studies to investigate whether selection on offspring survival due to cold snaps differs between nest box and natural post-fire populations.…”
Section: Discussionmentioning
confidence: 59%
“…The ultimate factors that promote use of cavity nests over drey nests by northern flying squirrels remain relatively uncertain (Smith 2012). Large DBH cavity-trees may be more widely used because they have more stable microclimates (Coombs et al 2010), provide better protection from inclement weather and predators (Smith 2007), or because they facilitate communal nesting. Large DBH trees with cavities represent a favorable habitat characteristic for northern flying squirrels in my study population and may be a limiting factor in areas where these features are lacking.…”
Section: Discussionmentioning
confidence: 99%